The Historical Context of Migration in Morocco to Europe: from Forced Migration to Irregular Migration : Study in International Law - Chouay, Hamza (Journal of Legal Sciences, 2023)
Considering that migration is moving to live from one place to another, with an intention in the place that was intended for a long time, due to the frequent movement of individuals from one place to another, and due to the different purpose of migration, we find external migration classified into legalized and irregular migration, and the reasons The growth of illegal immigration is due to economic, social, and psychological motives, and therefore we find that it has multiple effects, both on the country hosting immigrants in terms of economic, security, social and health terms, or on the level of organizing international relations between countries, so countries sought to mitigate this phenomenon and deal with immigrants As stipulated in its internal laws and in accordance with international law, while ensuring that their rights are not violated, and this is what Morocco has worked to achieve.